Complication profiles and their associated factors in Malaysian adult type 2 diabetes mellitus—an analysis of ADCM registry - Chew, Boon-How; Lee, Ping-Yein; Cheong, Ai-Theng; Ismail, Mastura; Bujang, Mohamad-Adam; Haniff, Jamaiyah; Taher, Sri-Wahyu; Goh, Pik-Pin (Research Society for Study of Diabetes in India, 2015)
Early detection and treatment of risk factors in type 2 diabetes mellitus (T2D) have been proven in reducing complications, improving survival and quality of life. This study aimed to examine an overall diabetes-related complication profiles and their associated factors in adult T2D. Adult diabetes control and management (ADCM) is a prospective registry that included patients with T2D in 2009. Complication profiles were reported descriptively. Multivariate analyses adjusted for differences in patient characteristics were used to determine the associated factors for diabetes-related complications categorised as microvascular complication (microCx) such as retinopathy and nephropathy and macrovascular complication (macroCx) such as ischaemic heart disease and cerebrovascular accident and both complications (combined microCx and macroCx). Complete data were available for 57,780 patients (81.5 %) with a mean age of 58.3 (SD 11.27) years; 59.7 % were female. About one fifth (10,834/57,780) of T2D patients were diagnosed with at least one complication. Ethnicity, gender, duration of T2D and co-morbids, under hospitals with specialist (HS) care, glycaemic and low-density lipoprotein-cholesterol (LDL-C) targets were associated with complications. When compared to T2D patients without complication, patients who were older (OR 1.03), male (OR 1.48), had longer duration of diabetes (OR 1.04) and hypertension (OR 1.03) and under the care HS (OR 13.64) were more likely to have both complications. T2D patients had moderate morbidity burden. Older age and male gender were two main risk factors of all types of complications. T2D patients with these associated factors should be monitored for prevention, screening and early treatment of diabetes-related complications. T2D patients under the HS care were noted to have also more complications could be due to HS had been centres of referral for advanced diabetes care rather than the result of HS care itself.